2019
DOI: 10.3390/molecules24203675
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Integrase Inhibitors Acting outside the Active Site Through High-Throughput Screening

Abstract: Currently, an increasing number of drugs are becoming available to clinics for the treatment of HIV infection. Even if this targeted therapy is highly effective at suppressing viral replication, caregivers are facing growing therapeutic failures in patients, due to resistance with or without treatment adherence concerns. Accordingly, it is important to continue to discover small molecules that have a novel mechanism of inhibition. In this work, HIV integrase inhibitors were selected by high-throughput screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In a more recent study, other stilbene disulfonic acids resulted to inhibit IN by a novel mechanism [77] (Fig. 13).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 90%
See 3 more Smart Citations
“…In a more recent study, other stilbene disulfonic acids resulted to inhibit IN by a novel mechanism [77] (Fig. 13).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 90%
“…Notably, preliminary in vivo studies reported in the literature have shown that in general, stilbenoids show low bioavailability and undergo extensive metabolism and it has been pointed out that bioconverted forms of polyphenols, (phase I and II metabolism) may probably have more importance than the parent compound found in the diet or administered in therapy. In many cases, synthetic efforts produced stilbene derivatives with greater potency than their parent compounds, allowing to expand knowledge on modes of action and to deepen structure-activity relationship studies of the most active compounds [39,70,76,77,82,91].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…His-tagged NL4-3 IN was expressed from a pET15b plasmid in the E. coli BL21 pLys strain. Recombinant protein was purified as previously described 67 following a batch preparation on Ni-NTA beads (Qiagen, Paris, France).…”
Section: Methodsmentioning
confidence: 99%